Anterior Traumatic Dental Injuries in East Iranian School Children: Prevalence and Risk Factors - Rouhani, Armita; Movahhed, Taraneh; Ghoddusi, Jamileh; Mohiti, Yones; Banihashemi, Elham; Akbari, Majid (Iranian Endodontic Journal, 2014)
Introduction: The aim of this cross-sectional study was to determine the prevalence and etiology of traumatic dental injuries (TDI) in school children of the Northeast of Iran. The type of involved teeth, the place of injury and treatment quality as well as the relationship between TDI and anatomic predisposing factors such as overjet and lip coverage were evaluated. Methods and Materials: A total of 778 school children were clinically examined for signs of trauma to their permanent teeth and the amount of overjet and lip coverage were also recorded. A questionnaire containing demographic data of participants and history of the dental trauma was given to the children’s parents. The data were analyzed using the chi-square and Mann-Whitney tests. Results: One hundred and seventy eight (22.9%) children had a history of previous trauma to their permanent teeth. There was a significant difference between boys and girls (P=0.017). A total of 46.1% of children had experienced luxation injuries of permanent teeth, 37% had crown fractures, and 16.9% experienced avulsion of anterior teeth. Maxillary central incisors were the most commonly affected teeth (84%). There was a significant relationship between TDI and overjet (P=0.02) in permanent teeth. On the other hand, there was no statistically significant relationship between TDI and lip coverage. The most common cause of TDI was falling over (42.9%) followed by fighting (34%). The majority of traumas happened at home (46.8%) and school (29.9%). Sixty two (39.7%) children with TDI did not receive any dental or medical care after injury. Conclusion: The prevalence of dental trauma in school children in Iran was rather high (22.9%); the most common type of trauma to the permanent teeth was luxation injuries.